Design and Implementation of Arduino Based Low-Cost Ventilator Using Self Inflating Bag - Khalaf, Mariam Hassan Zoued; Jaber, Hala Hilal Katea; Diwan, Alaq Talal Sameer; Sagat, Fatima Muwaffaq Hamid (American Journal of Botany and Bioengineering, 2025)
The global demand for cost-effective and accessible medical ventilators has increased significantly, especially in response to respiratory illnesses like COVID-19. This study explores the development of a DIY ventilator using Arduino, a microcontroller-based open-source platform. The proposed system integrates sensors, motors, and control algorithms to regulate airflow and maintain respiratory parameters within clinically acceptable ranges. By leveraging low-cost components and open-source hardware, this project aims to provide an affordable alternative for resource-limited settings. The paper discusses the design, implementation, and potential limitations of the system, emphasizing the importance of safety measures, reliability, and adaptability for different patient needs. While DIY ventilators cannot replace certified medical equipment, they present an innovative approach to emergency respiratory support and biomedical engineering education.